2019
DOI: 10.4102/sajr.v23i1.1707
|View full text |Cite
|
Sign up to set email alerts
|

Medical doctors’ awareness of radiation exposure in diagnostic radiology investigations in a South African academic institution

Abstract: BackgroundDiagnostic investigations using radiation have become a critical feature of medical practice in recent times. However, the possibility of doctors’ underestimation of risks of over-exposure of patients to diagnostic radiation still warrants further evaluation.ObjectivesTo investigate doctors’ awareness of diagnostic radiation exposure at Dr George Mukhari Academic Hospital, South Africa.MethodsThis was a cross-sectional, analytical investigation of the awareness of doctors about radiation exposure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
(31 reference statements)
0
19
0
1
Order By: Relevance
“…They also commented on the need to improve undergraduate NM training in South Africa. 46 Similarly, in a study done to investigate doctors’ awareness of diagnostic radiation exposure at Dr George Mukhari Academic Hospital Ga-Rankuwa, Pretoria, Dauda et al 8 reported that 80% of the 217 participants had no formal training on radiation exposure. Dauda and colleagues also advocated for improved teaching on radiation medicine at undergraduate level.…”
Section: The South African Perspectivementioning
confidence: 99%
See 4 more Smart Citations
“…They also commented on the need to improve undergraduate NM training in South Africa. 46 Similarly, in a study done to investigate doctors’ awareness of diagnostic radiation exposure at Dr George Mukhari Academic Hospital Ga-Rankuwa, Pretoria, Dauda et al 8 reported that 80% of the 217 participants had no formal training on radiation exposure. Dauda and colleagues also advocated for improved teaching on radiation medicine at undergraduate level.…”
Section: The South African Perspectivementioning
confidence: 99%
“…Dauda and colleagues also advocated for improved teaching on radiation medicine at undergraduate level. 8 …”
Section: The South African Perspectivementioning
confidence: 99%
See 3 more Smart Citations